Positive electrode active material and lithium secondary battery including the same

The bimodal type positive electrode active material, comprising a nickel-cobalt lithium complex oxide and a cobalt-free lithium complex oxide, addresses the challenge of reducing cobalt content in lithium secondary batteries, enhancing electrochemical properties and stability while lowering costs.

JP2025066078AActive Publication Date: 2025-04-22ECOPRO BM CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024175529
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-10-10
Filing Date
2024-10-07
Publication Date
2025-04-22
Estimated Expiration
2044-10-07

AI Technical Summary

Technical Problem

The increasing demand for lithium secondary batteries, particularly for electric vehicles, has led to a need for cost-reduced positive electrode active materials. However, commercialized ternary or quaternary lithium composite oxides rely heavily on cobalt, which is expensive and has supply chain instability, resulting in challenges with electrochemical properties and stability when reducing cobalt content.

Method used

A bimodal type positive electrode active material is developed, comprising a first lithium complex oxide with nickel and cobalt, and a second cobalt-free lithium complex oxide. This combination, along with a coating layer on the surface of the particles, improves electrochemical properties and stability, allowing for reduced cobalt content while maintaining performance.

Benefits of technology

The bimodal type positive electrode active material achieves improved electrochemical properties and stability compared to conventional low-cobalt or cobalt-free lithium composite oxides, effectively reducing the cobalt content and associated costs while maintaining performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025066078000001_ABST
    Figure 2025066078000001_ABST
Patent Text Reader

Abstract

To provide a positive electrode active material having improved electrochemical properties and stability and a lithium secondary battery including the same.SOLUTION: A positive electrode active material is a bimodal type positive electrode active material including a first lithium composite oxide and a second lithium composite oxide having different particle sizes and compositions, where the first lithium composite oxide includes first bulk particles including at least nickel and cobalt, and the second lithium composite oxide includes cobalt-free second bulk particles.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode active material and a lithium secondary battery including the same, and more specifically, to a bimodal type positive electrode active material including a first lithium composite oxide and a second lithium composite oxide having different particle sizes and compositions, and a lithium secondary battery including the same. [Background technology]

[0002] Batteries store electricity by using materials capable of electrochemical reactions at the positive and negative electrodes. A representative example of such batteries is a lithium secondary battery, which stores electrical energy by the difference in chemical potential when lithium ions are intercalated / deintercalated at the positive and negative electrodes.

[0003] The lithium secondary battery is manufactured by using a material capable of reversible intercalation / deintercalation of lithium ions as a positive electrode and a negative electrode active material, and filling an organic electrolyte or a polymer electrolyte between the positive electrode and the negative electrode.

[0004] Lithium composite oxides are used as the positive electrode active material in lithium secondary batteries, and examples of these include LiCoO 2 , LiMn 2 O 4 , LiNiO 2 , LiMnO 2 Composite oxides such as these are being researched.

[0005] Among the positive electrode active materials, LiCoO 2 is the most widely used due to its excellent life characteristics and charge / discharge efficiency, but has the disadvantage that its price competitiveness is limited because the cobalt used as a raw material is expensive.

[0006] LiMnO 2 , LiMn 2 O 4Lithium manganese oxides such as LiNiO have the advantages of being thermally safe and inexpensive, but they have problems such as small capacity and poor high-temperature properties. 2 Although the positive electrode active material based on this system has the advantage of exhibiting a high discharge capacity, it is difficult to synthesize due to active cation mixing of Li and Ni, and the rate characteristics and life characteristics of the synthesized positive electrode active material are very poor.

[0007] This resulted in LiNiO 2 In order to improve the low rate and life characteristics while maintaining the high reversible capacity of lithium composite oxides, ternary type lithium composite oxides such as NCM (Ni-Co-Mn) and NCA (Ni-Co-Al) or quaternary type lithium composite oxides such as NCMA (Ni-Co-Mn-Al) have been developed in which part of the nickel is replaced with cobalt, manganese and / or aluminum. The lower the nickel content in such ternary or quaternary type lithium composite oxides, the lower the reversible capacity, so recently, active research has been conducted to increase the nickel content in lithium composite oxides.

[0008] Commercially available ternary or quaternary type lithium composite oxides contain cobalt as an essential element in order to achieve a balance between electrochemical properties and particle stability, which are in a trade-off relationship with each other.

[0009] However, as the demand for lithium secondary batteries has grown rapidly recently and the cost of raw materials has increased, the lithium secondary battery market has faced a strong demand for cost reduction. In particular, the positive electrode active material accounts for the largest proportion of the cost in lithium secondary batteries, and cobalt, an essential element of ternary or quaternary type lithium composite oxides, is not only the most expensive metal but also has an unstable supply and demand, so the market demand for cost-reduced positive electrode active materials by adopting low-cobalt or cobalt-free compositions is increasing.

[0010] However, as described above, in commercially available ternary or quaternary type lithium composite oxides, cobalt is an element that is essentially required to achieve both electrochemical properties and particle stability.

[0011] For example, it has been reported that as the cobalt content in ternary or quaternary type lithium composite oxide decreases, the volumetric contraction / expansion of the lithium composite oxide during charging / discharging (egstress-causing anisotropic change) causes the formation of microcracks within the particles. As more microcracks form within the particles, electrolytes penetrate into the particles along the microcracks, accelerating particle decomposition, which leads to performance degradation of lithium secondary batteries.

[0012] In addition, as the cobalt content in ternary or quaternary type lithium composite oxide decreases, the resistance of the positive electrode active material increases and the rate characteristics decrease. Therefore, even if a low-cobalt (generally a cobalt content of 10 mol% or less) or cobalt-free composition is adopted, it is necessary to develop a positive electrode active material that maintains the electrochemical characteristics of the positive electrode active material at a similar level to that of commercially available positive electrode active materials. Summary of the Invention [Problem to be solved by the invention]

[0013] In the lithium secondary battery market, the growth of lithium secondary batteries for electric vehicles is playing a leading role in the market, and as a result, the demand for positive electrode active materials used in lithium secondary batteries is also continuously increasing.

[0014] For example, lithium secondary batteries using lithium iron phosphate (LFP) have been mainly used in the past due to safety concerns, but recently there has been a trend towards the use of nickel-based lithium composite oxides, which have a higher energy capacity per weight than LFP. Of course, relatively cheap LFP is still sometimes used to save costs.

[0015] Recently, nickel-based lithium composite oxides, which are mainly used as positive electrode active materials for high-capacity lithium secondary batteries, generally have a ternary type composition such as NCM (Ni-Co-Mn) and NCA (Ni-Co-Al) or a quaternary type composition such as NCMA (Ni-Co-Mn-Al). However, since the supply and demand of cobalt is unstable and it is excessively expensive compared to other raw materials, there is a need to develop a positive electrode active material with a low-cobalt or cobalt-free composition.

[0016] Recently, some manufacturers have introduced low-cobalt or cobalt-free cathode active materials, but the prevailing opinion is that their electrochemical properties and stability are still insufficient to replace conventional commercial cathode active materials.

[0017] For example, as described above, as the cobalt content in the ternary or quaternary type lithium composite oxide decreases, the resistance of the positive electrode active material increases, and the deterioration of electrochemical characteristics such as the rate characteristics of the lithium secondary battery is inevitable.

[0018] In addition, it has been pointed out that as the cobalt content in ternary or quaternary type lithium composite oxide decreases, the stability of the particles (crystal stability, thermal stability, particle strength, etc.) decreases rapidly, which may cause the life of a lithium secondary battery using the lithium composite oxide as a positive electrode active material to deteriorate early.

[0019] It is true that the electrochemical properties and stability of the conventional ternary or quaternary type lithium composite oxides that have been commercialized as low-cobalt or cobalt-free compositions are somewhat low. However, the present inventors have confirmed that a bimodal type positive electrode active material designed to contain a nickel-based lithium composite oxide containing cobalt and a cobalt-free lithium composite oxide can exhibit electrochemical properties and stability at a level that allows commercialization.

[0020] Accordingly, the present invention provides a bimodal type positive electrode active material including a first lithium composite oxide and a second lithium composite oxide having different particle sizes and compositions, in which a nickel-based lithium composite oxide and a cobalt-free lithium composite oxide are present in a bimodal form, thereby providing a positive electrode active material having improved electrochemical properties and stability compared to conventional lithium composite oxides having low-cobalt or cobalt-free compositions.

[0021] Another object of the present invention is to provide a positive electrode comprising the positive electrode active material defined herein.

[0022] It is yet another object of the present invention to provide a lithium secondary battery using the positive electrode defined herein.

[0023] The object of the present invention is not limited to the object mentioned above, and other objects and advantages of the present invention not mentioned can be understood from the following description and will be more clearly understood by the embodiments of the present invention. In addition, it will be easily known that the object and advantages of the present invention can be realized by the means and combinations thereof as set forth in the claims. [Means for solving the problem]

[0024] According to one aspect of the present invention for solving the above-mentioned technical problems, there is provided a bimodal type positive electrode active material including a first lithium composite oxide and a second lithium composite oxide having an average particle size larger than that of the first lithium composite oxide.

[0025] In one embodiment, the first lithium composite oxide may include first bulk particles containing at least nickel and cobalt, and the second lithium composite oxide may include second bulk particles that are cobalt-free.

[0026] In one embodiment, the first bulk particles may be represented by Formula 1 below.

[0027] [Chemical formula 1] Li w Ni 1-(x+y+z) Co x M1 y M2 z O 2 wherein M1 is at least one selected from Mn and Al, and M2 is at least one selected from P, Sr, Ba, B, Ce, Cr, Mn, Mo, Na, K, Ti, Zr, Al, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, Ca, Ga, Sb, Fe, Nd, and Cu, M1 and M2 are different from each other, and 0.5≦w≦1.5, 0 <x≦0.40、0≦y≦0.30、0≦z≦0.20である。

[0028] In one embodiment, the second bulk particles may be represented by Formula 2 below.

[0029] [Chemical formula 2] Li a Ni 1-(b+c) M3 b M4 c O 2-α X α Here, M3 is at least one selected from Mn and Al, M4 is at least one selected from Sr, Ba, B, Ce, Cr, Mn, Mo, Na, K, Ti, Zr, Al, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, Ca, Ga, Sb, Fe, Nd, and Cu, M3 and M4 are different elements from each other, X is at least one anionic element selected from F, P, S, Cl, and Br, and 0.5 ≦ a ≦ 1.5, 0 ≦ b ≦ 0.50, 0 ≦ c ≦ 0.20, 0 ≦ α ≦ 0.20.

[0030] In some embodiments, in order to improve the electrochemical properties and stability compared to conventional low-cobalt or cobalt-free lithium composite oxide compositions, a coating layer can be formed on the surface of the first bulk particles among the bimodal type cathode active materials.

[0031] Specifically, a coating layer is present on at least a part of the surface of the first bulk particles, and the coating layer may contain a metal oxide represented by the following Chemical Formula 3.

[0032] [Chemical Formula 3] Li d M5 e O f Here, M5 is at least one selected from Ni, Co, P, Sr, Ba, B, Ce, Cr, Mn, Mo, Na, K, Ti, Zr, Al, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, Ca, Ga, Sb, Fe, Nd, and Cu, 0 ≦ d ≦ 8, 0 < e ≦ 8, 0 < f ≦ 13, and d, e, f represent numbers determined from the stoichiometric ratio according to the valence of M5.

[0033] Further, by ensuring that cobalt is present at an appropriate level based on the overall composition of the bimodal-type cathode active material, the electrochemical properties and stability can be improved as compared to conventional low-cobalt or cobalt-free lithium composite oxides.

[0034] For this purpose, the coating layer present on the surface of the first bulk particles may contain a cobalt-containing oxide.

[0035] In another embodiment, in order to improve the electrochemical properties and stability as compared to conventional low-cobalt or cobalt-free lithium composite oxides, a coating layer can be formed on the surface of the second bulk particles among the bimodal-type cathode active materials. At this time, coating layers may be present on the surfaces of the first bulk particles and the second bulk particles among the cathode active materials.

[0036] Specifically, a coating layer is present on at least a part of the surface of the second bulk particles, and the coating layer may contain a metal oxide represented by the following Chemical Formula 4.

[0037] [Chemical Formula 4] Li g M6 h O i Here, M6 is at least one selected from Ni, Co, P, Sr, Ba, B, Ce, Cr, Mn, Mo, Na, K, Ti, Zr, Al, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, Ca, Ga, Sb, Fe, Nd, and Cu, 0 ≦ g ≦ 8, 0 < h ≦ 8, 0 < i ≦ 13, and g, h, and i represent numbers determined from the stoichiometric ratio according to the valence of M6.

[0038] In another embodiment, a coating layer is present on at least a portion of the surface of the second bulk particle, and the coating layer may include a compound represented by LiX' (X' is an anion element selected from F, Cl, and Br). For example, the compound represented by LiX' may include LiF. In yet another embodiment, the coating layer may include lithium sulfide, lithium sulfate, or lithium phosphate.

[0039] In addition, by making the cobalt present at an appropriate level based on the overall composition of the bimodal type positive electrode active material, it is possible to improve the electrochemical properties and stability compared to conventional lithium composite oxides having low-cobalt or cobalt-free compositions.

[0040] To this end, the coating layer present on the surface of the second bulk particles may comprise a cobalt-containing oxide.

[0041] According to another aspect of the present invention, there is provided a positive electrode including the above-described positive electrode active material.

[0042] According to yet another aspect of the present invention, there is provided a lithium secondary battery using the above-mentioned positive electrode. Effect of the Invention

[0043] According to the present invention, by providing a bimodal type positive electrode active material including a nickel-based lithium composite oxide (first lithium composite oxide) and a cobalt-free lithium composite oxide (second lithium composite oxide) having different particle sizes and compositions, more specifically, by providing a bimodal type positive electrode active material including a nickel-based lithium composite oxide (first lithium composite oxide) and a cobalt-free lithium composite oxide (second lithium composite oxide), it is possible to improve electrochemical properties and stability compared to conventional lithium composite oxides having low-cobalt or cobalt-free compositions.

[0044] In particular, by forming a predetermined coating layer on the surface of the first bulk particles constituting the first lithium composite oxide and / or the second bulk particles constituting the second lithium composite oxide, it is possible to contribute to improving the electrochemical properties and stability compared to conventional lithium composite oxides having low-cobalt or cobalt-free compositions.

[0045] When a coating layer containing a cobalt-containing oxide is formed on the surface of the first bulk particles constituting the first lithium composite oxide and / or the second bulk particles constituting the second lithium composite oxide, the cobalt content in the first bulk particles can be further reduced, and as a result, the cobalt content in the overall composition (bulk composition) of the bimodal type positive electrode active material can be reduced, thereby achieving the objective of reducing the cost of the positive electrode active material.

[0046] In addition, according to the present invention, by designing an appropriate metal composition of the nickel-based lithium composite oxide (first lithium composite oxide) and the cobalt-free lithium composite oxide (second lithium composite oxide) among the bimodal type positive electrode active materials, it is possible to further improve the electrochemical properties of the positive electrode active material. [Brief description of the drawings]

[0047] [Figure 1] FIG. 1 is a diagram showing dQ / dV profiles during initial discharge of a lithium secondary battery according to changes in the mole fractions of nickel and manganese in the positive electrode active material (lithium composite oxide). [Diagram 2] FIG. 2 is a diagram showing dQ / dV profiles during initial discharge of the lithium secondary batteries manufactured using the positive electrode active materials according to Examples 1 to 3, respectively. [Diagram 3] FIG. 3 is a diagram showing dQ / dV profiles during initial discharge of lithium secondary batteries manufactured using the positive electrode active materials according to Comparative Examples 1 to 3, respectively. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0048] In order to make the present invention easier to understand, certain terms are defined herein for convenience. Unless otherwise defined herein, scientific and technical terms used in the present invention shall have the meanings commonly understood by those of ordinary skill in the art. Furthermore, unless otherwise specified by the context, singular terms shall be understood to include their plural forms, and plural terms shall be understood to include their singular forms.

[0049] Hereinafter, the positive electrode active material according to the present invention and the lithium secondary battery including the positive electrode active material will be described in more detail.

[0050] positive electrode active material According to one aspect of the present invention, there is provided a bimodal type positive electrode active material including a first lithium composite oxide and a second lithium composite oxide which are different from each other in particle size and composition.

[0051] In one embodiment, the bimodal type positive electrode active material may include a first lithium composite oxide and a second lithium composite oxide having a larger average particle size than the first lithium composite oxide. The first lithium composite oxide having a relatively small average particle size may be referred to as a small particle, and the second lithium composite oxide having a relatively large average particle size may be referred to as a large particle.

[0052] The particle size distribution and average particle size of the first lithium composite oxide and the second lithium composite oxide of the positive electrode active material can be measured by a laser diffraction method. For example, the lithium composite oxide (small particles or large particles) is dispersed in a dispersion medium, introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000), and irradiated with ultrasonic waves of about 28 kHz at an output of 60 W to obtain a volume cumulative particle size distribution graph, and the particle size corresponding to 50% of the volume cumulative amount is determined as the average particle size (D 50In other cases, the average particle size of the first lithium composite oxide and the second lithium composite oxide of the positive electrode active material may be calculated as an average value of the particle sizes of small particles and large particles observed from a SEM image.

[0053] In the present application, the range of the average particle size (D50) of the small particles and the large particles is not particularly limited.

[0054] For example, the small particles may refer to lithium composite oxides having an average particle size (D50) of 7 μm or less, 6.5 μm or less, 6 μm or less, 5.5 μm or less, 5 μm or less, 4.5 μm or less, 4 μm or less, 3.5 μm or less, or 3 μm or less. In order to prevent the small particles from excessively agglomerating with each other, the average particle size (D50) of the small particles is preferably 0.5 μm or more, 1 μm or more, 1.5 μm or more, or 2 μm or more. For example, the large particles may refer to lithium composite oxides having an average particle size (D50) of more than 7 μm, 7.5 μm or more, 8 μm or more, 8.5 μm or more, 9 μm or more, 9.5 μm or more, 10 μm or more, 10.5 μm or more, 11 μm or more, 11.5 μm or more, or 12 μm or more. In order that the small particles having a relatively small average particle size are sufficiently packed in the gaps formed by the large particles, it is preferable that the average particle size (D50) of the large particles is 30 μm or less, 27.5 μm or less, 25 μm or less, 22.5 μm or less, 20 μm or less, 17.5 μm or less, or 15 μm or less.

[0055] In the bimodal type positive electrode active materials according to various embodiments of the present invention, the first lithium composite oxide and the second lithium composite oxide may be present in a mixed state in a weight ratio of 5:95, 10:90, 15:85, 20:80, 25:75, 30:70, 35:65, 40:60, 45:55, 50:50, 55:45, 60:40, 65:35, 70:30, 75:25, or 80:20, or the first lithium composite oxide and the second lithium composite oxide may be present in a mixed state in any weight ratio between 5:95 and 80:20.

[0056] In this case, the first lithium composite oxide may be present in a form filled in the gaps between the second lithium composite oxide, attached to the surface of the second lithium composite oxide, or in a form in which the first lithium composite oxides are aggregated together. However, it is preferable that the first lithium composite oxide having a relatively small average particle size is present in a state in which at least the gaps formed by a plurality of the second lithium composite oxides are sufficiently filled.

[0057] Since the gaps between the large particles are filled with small particles having a relatively small average particle size, the integration density of the lithium composite oxide in a unit volume is improved, and the energy density per unit volume can be increased. Also, since the gaps between the large particles are filled with small particles having a relatively small average particle size, volume change during charging and discharging can be mitigated, stress caused by volume change can be minimized, and microcracks can be prevented.

[0058] When the ratio of the first lithium composite oxide to the second lithium composite oxide in the positive electrode active material is too low, the first lithium composite oxide may not be sufficiently filled in the voids formed by the second lithium composite oxide. On the other hand, when the ratio of the first lithium composite oxide to the second lithium composite oxide in the positive electrode active material is too high, the ratio of the first lithium composite oxide aggregated in the positive electrode active material increases, and the press density of the positive electrode active material may decrease, thereby decreasing the stability of the positive electrode active material.

[0059] In one embodiment, the first lithium composite oxide may include first bulk particles containing at least nickel and cobalt, and the second lithium composite oxide may include cobalt-free second bulk particles. Here, bulk particles refer to single particles or secondary particles. The second bulk particles being cobalt-free means that the second bulk particles do not substantially contain cobalt. However, in some embodiments, when a coating layer is present on at least a portion of the surface of the second bulk particles, the coating layer may contain cobalt. Therefore, when a coating layer containing cobalt is present on at least a portion of the surface of the second bulk particles, but the second bulk particles do not contain cobalt, the second bulk particles may be defined as having a cobalt-free composition. The second lithium composite oxide may also include cobalt-free second bulk particles containing at least nickel and manganese.

[0060] For example, the particles having the average particle size and composition defined as the first lithium composite oxide and the second lithium composite oxide may be single particles in a non-aggregated state or secondary particles in the form of aggregation of multiple primary particles. In this case, both the single particles and the secondary particles can be referred to as bulk particles.

[0061] Therefore, the first bulk particles refer to single particles and secondary particles having an average particle size and composition defined as the first lithium composite oxide, and the second bulk particles refer to single particles and secondary particles having an average particle size and composition defined as the second lithium composite oxide.

[0062] As described above, in the case of a bimodal type positive electrode active material, the gaps between large particles are filled with small particles having a relatively small average particle size, thereby improving the integration density of lithium composite oxide within a unit volume, increasing the energy density per unit volume, reducing stress due to volumetric changes during charging and discharging, and preventing the occurrence of microcracks.

[0063] However, small particles of bimodal type positive electrode active materials have a relatively larger specific surface area than large particles, so there is a higher possibility of side reactions with the electrolyte (for example, an initial irreversible reaction that forms a solid electrolyte interphase (SEI)). Due to this side reaction mechanism, the degradation rate of small particles can be faster than that of large particles. In addition, in the case of lithium composite oxides that have the possibility of manganese leaching at high temperatures, the larger the specific surface area, the more the leaching of manganese can be activated, which can accelerate the deterioration of the life due to repeated charging and discharging.

[0064] Therefore, the first bulk particles as small particles have a composition containing at least nickel and cobalt, and the second bulk particles as large particles have a cobalt-free composition, which improves the electrochemical properties and stability compared to conventional lithium composite oxides having low-cobalt or cobalt-free compositions, and as a result, is advantageous in reducing the cobalt content in the overall composition (bulk composition) of the bimodal type positive electrode active material, thereby achieving the goal of reducing the cost of the positive electrode active material.

[0065] It is preferred that the mole fraction of nickel in the first bulk particles is greater than the mole fraction of nickel in the second bulk particles, and the mole fraction of manganese in the first bulk particles is less than the mole fraction of manganese in the second bulk particles.

[0066] In order to evaluate the electrochemical properties or behavior of a positive electrode active material, a dQ / dV graph, which is the differentiation of the battery capacity with respect to the voltage after charging and discharging, is often used. For example, when a lithium secondary battery including a positive electrode using any lithium composite oxide containing nickel and manganese as a positive electrode active material and a negative electrode using lithium foil as a negative electrode is charged and discharged at 25°C, voltage range 3.0V to 4.4V, and discharge rate of 0.1C, a peak indicating the presence of H2 (hexagonal2) → H3 (hexagonal3) phase transformation is observed in the charging region of 4.1V to 4.3V in a graph showing voltage (V) and battery capacity (Q) at the time of initial discharge, with the X-axis being the voltage (V) and the Y-axis being the battery capacity (Q), and the value (dQ / dV) obtained by differentiating the battery capacity (Q) with respect to the voltage (V). In general, as the mole fraction of manganese in the lithium composite oxide increases, the voltage band where the H2→H3 peak is observed shifts to a relatively higher voltage. For example, when the mole fraction of manganese in the lithium composite oxide is about 10%, the H2→H3 peak is observed at about 4.21 V, but when the mole fraction of manganese increases to about 20%, the H2→H3 peak is observed at about 4.26 V.

[0067] In this way, the more the voltage band where the H2→H3 peak is observed in the dQ / dV profile for a given positive electrode active material is shifted to the right, the more the positive electrode active material can exhibit an appropriate capacity at a relatively high voltage. As the voltage band where the positive electrode active material can exhibit an appropriate capacity becomes higher, problems such as reduced stability or early deterioration of the positive electrode active material may occur, and problems such as accelerated gas generation due to side reactions may also occur.

[0068] Therefore, according to an embodiment of the present invention, by providing a bimodal type positive electrode active material in which the mole fraction of nickel in the first bulk particles is greater than the mole fraction of nickel in the second bulk particles and the mole fraction of manganese in the first bulk particles is less than the mole fraction of manganese in the second bulk particles, it is possible to reduce the voltage range in which the positive electrode active material can exhibit an appropriate capacity.

[0069] The first bulk particles are represented by the following Chemical Formula 1 and are lithium composite oxides having a layered crystal structure.

[0070] [Chemical formula 1] Li w Ni 1-(x+y+z) Co x M1 y M2 z O 2 wherein M1 is at least one selected from Mn and Al, and M2 is at least one selected from P, Sr, Ba, B, Ce, Cr, Mn, Mo, Na, K, Ti, Zr, Al, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, Ca, Ga, Sb, Fe, Nd, and Cu, M1 and M2 are different from each other, and 0.5≦w≦1.5, 0 <x≦0.40、0≦y≦0.30、0≦z≦0.20である。

[0071] The ratio w of lithium to all elements other than lithium in the first bulk particles may be 0.5 to 1.5, 0.75 to 1.25, 0.90 to 1.1, or 0.95 to 1.05.

[0072] In one embodiment, the first bulk particles may be a lithium-nickel-based composite oxide having a mole fraction of nickel of 60% or more relative to all elements other than lithium in the first bulk particles, where x+y+z in Formula 1 is 0.40 or less.

[0073] In other embodiments, the molar fraction of nickel relative to all elements other than lithium in the first bulk particles may be 65% or more (in this case, x+y+z is 0.35 or less), 70% or more (in this case, x+y+z is 0.30 or less), 75% or more (in this case, x+y+z is 0.25 or less), 80% or more (in this case, x+y+z is 0.20 or less), 85% or more (in this case, x+y+z is 0.15 or less) or 90% or more (in this case, x+y+z is 0.10 or less).

[0074] The molar fraction of cobalt relative to all elements other than lithium in the first bulk particles may be 40% or less (in this case, x is 0.40 or less), 35% or less (in this case, x is 0.35 or less), 30% or less (in this case, x is 0.30 or less), 25% or less (in this case, x is 0.25 or less), 20% or less (in this case, x is 0.20 or less), 15% or less (in this case, x is 0.15 or less), or 10% or less (in this case, x is 0.10 or less).

[0075] When the first bulk particles contain manganese and / or aluminum, the molar fraction of manganese and / or aluminum relative to all elements other than lithium in the first bulk particles may be 30% or less (in this case, y is 0.30 or less), 25% or less (in this case, y is 0.25 or less), 20% or less (in this case, y is 0.20 or less), 15% or less (in this case, y is 0.15 or less), 10% or less (in this case, y is 0.10 or less), or 5% or less (in this case, y is 0.05 or less).

[0076] In addition, a dopant (M2) may be included in the first bulk particles for the purpose of improving the electrochemical properties of the first bulk particles.

[0077] When the first bulk particles selectively include a dopant, the dopant may include at least one selected from P, Sr, Ba, B, Ce, Cr, Mn, Mo, Na, K, Ti, Zr, Al, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, Ca, Ga, Sb, Fe, Nd, and Cu, or at least one selected from P, Sr, Ba, B, Ce, Cr, Mo, Na, K, Ti, Zr, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, Ca, Ga, Sb, Fe, Nd, and Cu. The type and combination of the dopant may be appropriately selected within a range that does not negatively affect the electrochemical properties and stability of the first bulk particles as well as the bimodal type positive electrode active material including the first bulk particles and the second bulk particles.

[0078] When the first bulk particles contain a dopant, the molar fraction of the dopant relative to all elements other than lithium in the first bulk particles may be 20% or less (in this case, z is 0.20 or less), 10% or less (in this case, z is 0.10 or less), 5% or less (in this case, z is 0.05 or less), 4% or less (in this case, z is 0.04 or less), 3% or less (in this case, z is 0.03 or less), 2% or less (in this case, z is 0.02 or less), 1% or less (in this case, z is 0.01 or less), 0.5% or less (in this case, z is 0.005 or less), 0.4% or less (in this case, z is 0.004 or less), 0.3% or less (in this case, z is 0.003 or less), 0.2% or less (in this case, z is 0.002 or less), or 0.1% or less (in this case, z is 0.001 or less).

[0079] The upper and lower limits of the contents of nickel, cobalt, M1 and M2 defined in the above Chemical Formula 1 can be appropriately selected within the ranges that satisfy the above definitions.

[0080] The second bulk particles are represented by the following Chemical Formula 2 and are lithium composite oxides having a layered crystal structure.

[0081] [Chemical formula 2] Li a Ni 1-(b+c) M3 b M4 c O 2-α X α wherein M3 is at least one selected from Mn and Al; M4 is at least one selected from Sr, Ba, B, Ce, Cr, Mn, Mo, Na, K, Ti, Zr, Al, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, Ca, Ga, Sb, Fe, Nd, and Cu; M3 and M4 are elements different from each other; X is at least one anion element selected from F, P, S, Cl, and Br; and 0.5≦a≦1.5, 0≦b≦0.50, 0≦c≦0.20, and 0≦α≦0.20.

[0082] The ratio a of lithium to all elements other than lithium in the second bulk particles may be 0.5 to 1.5, 0.75 to 1.25, 0.90 to 1.1, or 0.95 to 1.05.

[0083] As shown in Chemical Formula 2, at least a portion of the oxygen in the second bulk particles may be substituted with at least one anionic element selected from F, P, S, Cl and Br, preferably F. In particular, F has an ionic radius similar to that of oxygen and is more stable in the crystal structure of the second bulk particles than other anionic elements. In addition, F partially substitutes for oxygen forming M(metal)-O bonds to form strong M bonds, which can contribute to strengthening the crystal structure of the second bulk particles that has been weakened by the elimination of cobalt.

[0084] In an embodiment, the mole fraction of nickel (corresponding to “1−(b+c)” in Chemical Formula 2) in the metal elements excluding lithium in the second bulk particles may be 0.50 to 0.95, 0.60 to 0.90, or 0.70 to 0.80.

[0085] When M3 in the above Chemical Formula 2 is manganese, the molar fraction of manganese in the metal elements excluding lithium in the second bulk particles (corresponding to "b" in Chemical Formula 2) may be 0.05 to 0.50, 0.10 to 0.40, or 0.10 to 0.30. In this case, b+c in Chemical Formula 2 may be 0.50 or less, 0.45 or less, 0.40 or less, 0.35 or less, or 0.30 or less.

[0086] When the mole fraction of nickel in the second bulk particles is less than 0.50, the ratio of lithium composite oxide having a spinel crystal structure in the second bulk particles may be high. As the ratio of lithium composite oxide having a spinel crystal structure in the second bulk particles is high, a higher operating voltage is required, and the capacity characteristics of a lithium secondary battery using the second bulk particles as a positive electrode active material may be reduced. In addition, as the content of nickel in the second bulk particles is reduced, the manganese content increases, which may increase overall cation mixing in the lithium composite oxide.

[0087] Specifically, the charge of the entire transition metal constituting the lithium composite oxide is preferably in a trivalent state in order to exhibit a stable charge neutrality state. In this case, when synthesizing a lithium composite oxide having a low cobalt content and a high manganese content, Mn 4+ is in excess, so to indicate a charge neutral state, Ni 3+ Instead of Ni 2+ The content of Ni increases. 2+ (0.69Å) is Li + (0.76 Å), they can occupy the Li 3a site in the crystal structure of the lithium composite oxide, and this occupancy phenomenon is called cation mixing.

[0088] On the other hand, when the second bulk particles contain excessively large amounts of nickel, the lithium composite oxide is LiNiO 2 It shows the following characteristics: 2 Not only does it have low thermal stability, but if an internal short circuit occurs due to external pressure or the like while the battery is being charged, the lithium composite oxide may decompose itself, or a side reaction may occur at the interface or surface of the electrolyte and the lithium composite oxide, which may lead to the lithium secondary battery exploding or catching fire.

[0089] If the mole fraction of manganese in the second bulk particles is more than 0.50, the same problems as those occurring when the mole fraction of nickel is less than 0.50 may occur.

[0090] Additionally, a dopant (M4) may be included in the second bulk particles for the purpose of improving the electrochemical properties of the second bulk particles having a cobalt-free composition.

[0091] When the second bulk particles selectively include a dopant, the dopant may include at least one selected from Sr, Ba, B, Ce, Cr, Mn, Mo, Na, K, Ti, Zr, Al, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, Ca, Ga, Sb, Fe, Nd, and Cu, or Sr, Ba, B, Ce, Cr, Mo, Na, K, Ti, Zr, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, Ca, Ga, Sb, Fe, Nd, and Cu. The type and combination of the dopant may be appropriately selected within a range that does not negatively affect the electrochemical properties and stability of the bimodal type positive electrode active material including the second bulk particles, the first bulk particles, and the second bulk particles.

[0092] When the second bulk particles contain a dopant, the molar fraction of the dopant relative to all elements other than lithium in the second bulk particles may be 20% or less (in this case, c is 0.20 or less), 10% or less (in this case, c is 0.10 or less), 5% or less (in this case, c is 0.05 or less), 4% or less (in this case, c is 0.04 or less), 3% or less (in this case, c is 0.03 or less), 2% or less (in this case, c is 0.02 or less), 1% or less (in this case, c is 0.01 or less), 0.5% or less (in this case, c is 0.005 or less), 0.4% or less (in this case, c is 0.004 or less), 0.3% or less (in this case, c is 0.003 or less), 0.2% or less (in this case, c is 0.002 or less), or 0.1% or less (in this case, c is 0.001 or less).

[0093] In some embodiments, in order to improve the electrochemical properties and stability compared to conventional low-cobalt or cobalt-free lithium composite oxide compositions, a coating layer can be formed on the surface of the first bulk particles among the bimodal type cathode active materials. At this time, a coating layer may selectively exist on the surface of the second bulk particles.

[0094] Specifically, a coating layer exists on at least a part of the surface of the first bulk particles, and the coating layer may contain a metal oxide represented by the following Chemical Formula 3. The metal oxide represented by the following Chemical Formula 3 is an oxide having a composition different from that of the first bulk particles.

[0095] [Chemical Formula 3] Li d M5 e O f Here, M5 is at least one selected from Ni, Co, P, Sr, Ba, B, Ce, Cr, Mn, Mo, Na, K, Ti, Zr, Al, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, Ca, Ga, Sb, Fe, Nd, and Cu, preferably one or two elements. d, e, and f represent numbers determined from the stoichiometric ratio depending on the valence of M5. For example, d, e, and f can be appropriately selected in the ranges of 0 ≦ d ≦ 8, 0 < e ≦ 8, and 0 < f ≦ 13, respectively.

[0096] Also, by ensuring that cobalt is present at an appropriate level based on the overall composition of the bimodal type cathode active material, the electrochemical properties and stability can be improved compared to conventional low-cobalt or cobalt-free lithium composite oxide compositions.

[0097] For this purpose, the coating layer present on the surface of the first bulk particles may contain a cobalt-containing oxide. The cobalt-containing oxide is Co e O fand / or Li d Co e O f may be represented by

[0098] When a coating layer containing cobalt-containing oxide is formed on the surface of the first bulk particle, the molar fraction of cobalt in the metal elements excluding lithium based on the overall composition of the first bulk particle and the coating layer may be 0.15 or less, preferably 0.11 or less.

[0099] In other embodiments, in order to improve the electrochemical properties and stability compared to conventional low-cobalt or cobalt-free lithium composite oxides, a coating layer can be formed on the surface of the second bulk particle among the bimodal type cathode active materials. At this time, coating layers may be present on the surfaces of the first bulk particle and the second bulk particle among the cathode active materials.

[0100] Specifically, a coating layer may be present on at least a part of the surface of the second bulk particle, and the coating layer may contain a metal oxide represented by the following Chemical Formula 4. The metal oxide represented by the following Chemical Formula 4 is an oxide having a composition different from that of the second bulk particle.

[0101] [Chemical Formula 4] Li g M6 h O i Here, M6 is at least one selected from Ni, Co, P, Sr, Ba, B, Ce, Cr, Mn, Mo, Na, K, Ti, Zr, Al, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, Ca, Ga, Sb, Fe, Nd, and Cu, preferably one or two elements. g, h, and i represent numbers determined from the stoichiometric ratio according to the valence of M6. For example, g, h, and i can be appropriately selected in the ranges of 0 ≦ g ≦ 8, 0 < h ≦ 8, and 0 < i ≦ 13, respectively.

[0102] In addition, by making the cobalt present at an appropriate level based on the overall composition of the bimodal type positive electrode active material, it is possible to improve the electrochemical properties and stability compared to conventional lithium composite oxides having low-cobalt or cobalt-free compositions.

[0103] For this purpose, the coating layer present on the surface of the second bulk particle may include a cobalt-containing oxide. e O f and / or Li d Co e O f It can be displayed as:

[0104] As described above, the second bulk particles being cobalt-free means that the second bulk particles do not substantially contain cobalt. However, as defined above, even if a coating layer containing cobalt is present on at least a portion of the surface of the second bulk particles, the second bulk particles do not contain cobalt, so the second bulk particles may be a cobalt-free lithium composite oxide.

[0105] When a coating layer containing a cobalt-containing oxide is formed on the surface of the second bulk particles, the molar fraction of cobalt in metal elements excluding lithium based on the overall composition including the second bulk particles and the coating layer may be 0.05 or less, 0.04 or less, 0.03 or less, or 0.02 or less.

[0106] In another embodiment, a coating layer may be present on at least a portion of the surface of the second bulk particles, and the coating layer may include a compound represented by LiX' (X' is an anion selected from F, Cl, and Br). For example, the compound represented by LiX' may include LiF. LiF is a fluorine-containing polymer and lithium impurities (e.g., LiOH and Li) present on the surface of the second bulk particles. 2 CO 3In yet another embodiment, the coating layer may include lithium sulfide, lithium sulfate, or lithium phosphate. In the case of lithium phosphate, it may optionally include a metal element. The metal element may be at least one metal element selected from M3 and M4.

[0107] The molar fraction of cobalt in metal elements excluding lithium based on the overall composition (bulk composition) of the positive electrode active material including the first lithium composite oxide and the second lithium composite oxide may be 0.005 to 0.05, 0.005 to 0.045, 0.005 to 0.040, 0.005 to 0.035, 0.01 to 0.045, 0.01 to 0.040, or 0.01 to 0.035. In the present application, the term "overall composition (bulk composition) of the positive electrode active material" refers to the average composition of the first lithium composite oxide and the second lithium composite oxide constituting the bimodal type positive electrode active material.

[0108] When the molar fraction of cobalt is less than 0.005 based on the overall composition of the bimodal type positive electrode active material, the particle stability (crystal stability, thermal stability, particle strength, etc.) of the first lithium composite oxide and the second lithium composite oxide is insufficient, which may cause a problem in exhibiting stable electrochemical characteristics of the lithium secondary battery. Meanwhile, when the molar fraction of cobalt is more than 0.05 based on the overall composition of the bimodal type positive electrode active material, it is not consistent with the purpose of the present invention, which aims to improve electrochemical characteristics and stability compared to conventional lithium composite oxides having low-cobalt or cobalt-free compositions, and thereby reduce the cobalt content in the overall composition (bulk composition) of the bimodal type positive electrode active material, thereby reducing the cost of the positive electrode active material.

[0109] In addition, the molar fraction of manganese in metal elements excluding lithium based on the overall composition (bulk composition) of the bimodal-type positive electrode active material containing the first lithium composite oxide and the second lithium composite oxide may be 0.10 or more and 0.40 or less, 0.10 or more and 0.35 or less, 0.10 or more and 0.30 or less, 0.10 or more and 0.25 or less, 0.15 or more and 0.35 or less, 0.15 or more and 0.35 or less, 0.15 or more and 0.30 or less, 0.15 or more and 0.25 or less, 0.17 or more and 0.40 or less, 0.17 or more and 0.35 or less, 0.17 or more and 0.30 or less, or 0.17 or more and 0.25 or less.

[0110] When the mole fraction of manganese based on the overall composition of the bimodal type positive electrode active material is less than 0.10, the capacity characteristics (especially the discharge capacity) and rate characteristics of the bimodal type positive electrode active material are insufficient. On the other hand, when the mole fraction of manganese based on the overall composition of the bimodal type positive electrode active material is more than 0.40, the voltage range in which the positive electrode active material can exhibit an appropriate capacity may become excessively high.

[0111] When the manganese content is controlled within the above-mentioned range based on the overall composition (bulk composition) of the bimodal type positive electrode active material including the first lithium composite oxide and the second lithium composite oxide, a lithium secondary battery using the positive electrode active material is characterized by exhibiting the following dQ / dV behavior:

[0112] Specifically, when a lithium secondary battery having the positive electrode active material as a positive electrode and a lithium foil as a negative electrode is charged and discharged at 25° C., in a voltage range of 3.0 V to 4.4 V, and at a discharge rate of 0.1 C, a graph showing voltage (V) and battery capacity (Q) at the time of initial discharge, with the X-axis representing the voltage (V) and the Y-axis representing the battery capacity (Q), and the value (dQ / dV) obtained by differentiating the battery capacity (Q) with respect to the voltage (V), may have a peak in a charging region in a voltage range of 4.1 V to 4.2 V (more specifically, 4.2 V or lower).

[0113] Generally, the peaks present in the charging region of the voltage range of 4.1 V to 4.3 V are peaks indicating the presence of H2 (hexagonal 2) → H3 (hexagonal 3) phase transformation. In this case, as the mole fraction of manganese in the lithium composite oxide increases, the voltage range where the H2 → H3 peaks are observed shifts to a relatively higher voltage. For example, referring to FIG. 1 (NM99-Ni:Mn=99:1; NM90-Ni:Mn=90:10; NM80-Ni:Mn=80:20; NM70-Ni:Mn=70:30; NM60-Ni:Mn=60:40), which shows the dQ / dV profile during initial discharge of a lithium secondary battery depending on the mole fraction of nickel and manganese in the positive electrode active material (lithium composite oxide), when the mole fraction of manganese in the lithium composite oxide is about 10%, the H2→H3 peak is observed at about 4.21 V, but when the mole fraction of manganese increases to about 20%, the H2→H3 peak shifts to a higher voltage band and is observed at about 4.26 V.

[0114] As described above, when the cobalt content is reduced in a commercially available ternary or quaternary type lithium composite oxide, the nickel or manganese content is increased. In particular, when the manganese content in the lithium composite oxide is increased, the voltage range in which the positive electrode active material can exhibit the appropriate capacity becomes higher, which may cause early deterioration of the positive electrode active material, which is vulnerable to a high voltage operating environment. In addition, in order to reduce the risk of such a high voltage operating environment, a problem may arise in which the commercially available electrolyte and / or anode must be changed.

[0115] However, according to an embodiment of the present invention, a bimodal type positive electrode active material including a nickel-based lithium composite oxide (first lithium composite oxide) and a cobalt-free lithium composite oxide (second lithium composite oxide) is provided, so that the voltage range in which the positive electrode active material can exhibit an appropriate capacity can be shifted to a low voltage region (preferably, 4.2 V or less).

[0116] Lithium secondary battery According to another aspect of the present invention, a positive electrode may be provided, the positive electrode including a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector. Here, the positive electrode active material layer may include a positive electrode active material according to various embodiments of the present invention. Therefore, since the positive electrode active material is the same as that described above, detailed description will be omitted for convenience, and only the remaining components not described above will be described below.

[0117] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may usually have a thickness of 3 to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive strength of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0118] The positive electrode active material layer may be prepared by coating a positive electrode slurry composition containing the positive electrode active material, a conductive material, and optionally a binder, on the positive electrode current collector.

[0119] At this time, the positive electrode active material may be included in a content of 80 wt% to 99 wt%, more specifically, 85 wt% to 98.5 wt%, based on the total weight of the positive electrode active material layer, and excellent capacity characteristics can be exhibited when the content is within this range, but is not necessarily limited thereto.

[0120] The conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the battery that is constructed. Specific examples include graphite such as natural graphite and artificial graphite, carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon-based materials such as carbon fibers, metal powders or metal fibers such as copper, nickel, aluminum, and silver, conductive whiskers such as zinc oxide and potassium titanate, conductive metal oxides such as titanium oxide, and conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in combination. The conductive material may be contained in an amount of 0.1 wt% to 15 wt% based on the total weight of the positive electrode active material layer.

[0121] The binder serves to improve the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof, and among these, one type alone or a mixture of two or more types may be used. The binder may be included in an amount of 0.1 to 15 wt% based on the total weight of the positive electrode active material layer.

[0122] The positive electrode may be manufactured by a typical method for manufacturing a positive electrode, except for using the positive electrode active material. Specifically, the positive electrode may be manufactured by dissolving or dispersing the positive electrode active material and, optionally, a binder and a conductive material in a solvent to prepare a positive electrode slurry composition, which is then coated on a positive electrode current collector, followed by drying and rolling.

[0123] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, and to provide a viscosity that allows excellent thickness uniformity when applied to manufacture a positive electrode, taking into consideration the coating thickness of the slurry and the production yield.

[0124] In another embodiment, the positive electrode may be manufactured by casting the positive electrode slurry composition on a separate support, peeling the positive electrode slurry composition from the support, and laminating the resulting film on a positive electrode current collector.

[0125] According to yet another aspect of the present invention, there may be provided an electrochemical device including the above-mentioned positive electrode. The electrochemical device may be, for example, a battery or a capacitor, and more specifically, a lithium secondary battery.

[0126] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode facing the positive electrode, and a separator and an electrolyte interposed between the positive electrode and the negative electrode. Here, since the positive electrode is as described above, a detailed description thereof will be omitted for convenience, and only the remaining components not described above will be described in detail below.

[0127] The lithium secondary battery may optionally further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.

[0128] The negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0129] The negative electrode current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may generally have a thickness of 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector may be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.

[0130] The negative electrode active material layer may be prepared by coating a negative electrode slurry composition containing the negative electrode active material, a conductive material, and optionally a binder, on the negative electrode current collector.

[0131] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon, metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys, and SiO β (0<β<2), SnO 2, a metal oxide capable of doping and dedoping lithium, such as vanadium oxide or lithium vanadium oxide, or a composite containing the metallic compound and a carbonaceous material, such as a Si-C composite or a Sn-C composite, may be used. Any one or a mixture of two or more of these may be used. A thin film of metallic lithium may be used as the negative electrode active material. In addition, both low-crystalline carbon and high-crystalline carbon may be used as the carbon material. Representative examples of low-crystalline carbon include soft carbon and hard carbon, and representative examples of high-crystalline carbon include amorphous, plate-like, scaly, spherical or fibrous natural graphite or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes.

[0132] The negative electrode active material may be included in an amount of 80 wt % to 99 wt % based on the total weight of the negative electrode active material layer.

[0133] The binder is a component that aids in bonding between the conductive material, the active material, and the current collector, and may be added in an amount of 0.1 wt% to 10 wt% based on the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.

[0134] The conductive material may be added as a component for further improving the conductivity of the negative electrode active material in an amount of 10 wt% or less, preferably 5 wt% or less, based on the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it has conductivity without inducing a chemical change in the battery, and may be, for example, graphite such as natural graphite or artificial graphite, carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black, conductive fibers such as carbon fibers or metal fibers, metal powders such as carbon fluoride, aluminum, or nickel powder, conductive whiskers such as zinc oxide or potassium titanate, conductive metal oxides such as titanium oxide, or conductive materials such as polyphenylene derivatives.

[0135] In one embodiment, the negative electrode active material layer may be prepared by coating a negative electrode slurry composition prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent on a negative electrode current collector and drying the coating. Alternatively, the negative electrode slurry composition may be cast on a separate support, and then peeled off from the support to obtain a film, which may be laminated on the negative electrode current collector.

[0136] In another embodiment, the negative electrode active material layer may be manufactured by coating a negative electrode slurry composition prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent on a negative electrode current collector and drying the coating, or by casting the negative electrode slurry composition on a separate support and peeling the composition from the support to obtain a film, which may be laminated on the negative electrode current collector.

[0137] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode to provide a passage for lithium ions to move. Any separator generally used in lithium secondary batteries may be used without any particular limitation. In particular, it is preferable that the separator has low resistance to ion movement of the electrolyte and has excellent electrolyte humidification ability. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high-melting point glass fiber, a polyethylene terephthalate fiber, or the like, may be used. In addition, in order to ensure heat resistance or mechanical strength, a separator coated with a ceramic component or a polymer material may be used, and may be selectively used as a single-layer or multi-layer structure.

[0138] Furthermore, examples of the electrolyte used in the present application include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the manufacture of lithium secondary batteries, but are not limited to these.

[0139] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0140] The organic solvent may be used without any particular limitation as long as it serves as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone, an ether solvent such as dibutyl ether or tetrahydrofuran, a ketone solvent such as cyclohexanone, an aromatic hydrocarbon solvent such as benzene or fluorobenzene, dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Examples of the solvents that may be used include carbonate-based solvents such as ethylene carbonate (PC), alcohol-based solvents such as ethyl alcohol and isopropyl alcohol, nitriles such as R-CN (R is a straight-chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can improve the charge / discharge performance of a battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred. In this case, the performance of the electrolyte may be excellent if the cyclic carbonate and the chain carbonate are mixed at a volume ratio of about 1:1 to about 1:9.

[0141] The lithium salt may be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. 6 , LiClO 4 , LiAsF 6 , LiBF 4 , LiSbF 6 , LiAlO 4 , LiAlCl 4 , LiCF 3 SO 3 , LiC 4 F 9 SO 3 , LiN(C 2 F 5 SO 3 ), LiN(C 2 F 5 SO 2 ) 2 , LiN(CF 3 SO 2 ) 2 , LiCl, LiI, or LiB(C 2 O 4 ) 2 The lithium salt may be used at a concentration within the range of 0.1 to 2.0 M. When the lithium salt concentration is within this range, the electrolyte has appropriate conductivity and viscosity, and therefore excellent electrolyte performance can be exhibited, and lithium ions can migrate effectively.

[0142] When the electrolyte used in the present application is a solid electrolyte, for example, a solid inorganic electrolyte such as a sulfide-based solid electrolyte, an oxide-based solid electrolyte, a nitride-based solid electrolyte, or a halide-based solid electrolyte may be used, and preferably, a sulfide-based solid electrolyte may be used.

[0143] As the material of the sulfide-based solid electrolyte, a solid electrolyte containing Li, an X element (wherein X is at least one selected from P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In) and S may be used. Examples of the sulfide-based solid electrolyte material include Li 2 SP2 S 5 , Li 2 SP 2 S-LiX (where X is a halogen element such as I or Cl), Li 2 SP 2 S 5 -Li 2 O, Li 2 SP 2 S 5 -Li 2 O-LiI, Li 2 S-SiS 2 , Li 2 S-SiS 2 - LiI, Li 2 S-SiS 2 -LiBr, Li 2 S-SiS 2 -LiCl, Li 2 S-SiS 2 -B 2 S 3 - LiI, Li 2 S-SiS 2 -P 2 S5-LiI, Li 2 S.B. 2 S 3 , Li 2 SP 2 S 5 -ZmSn (where m and n are integers and Z is Ge, Zn or Ga), Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 2 S-SiS 2 -Li p MO q (where p, q are integers and M is P, Si, Ge, B, Al, Ga or In).

[0144] The solid electrolyte, preferably the sulfide-based solid electrolyte, may be amorphous or crystalline, or may be in a mixed amorphous and crystalline state.

[0145] As a material for oxide-based solid electrolytes, Li7 La 3 Zr 2 O 12 , Li 7-x La 3 Zr 1-x Nb x O 12 , Li 7-3x La 3 Zr 2 Al x O 12 , Li 3x La 2 / 3-x TiO 3 , Li 1+x Al x Ti 2-x (PO 4 ) 3 , Li 1+x Al x Ge 2-x (PO 4 ) 3 , Li 3 PO 4 , Li 3+x PO 4-x N x (LiPON), Li 2+2x Zinc 1-x GeO 4 (LISICON), etc.

[0146] The solid electrolyte may be disposed as a separate layer (solid electrolyte layer) between the positive electrode and the negative electrode. The solid electrolyte may be included in a portion of the positive electrode active material layer of the positive electrode, independent of the solid electrolyte layer, or the solid electrolyte may be included in a portion of the negative electrode active material layer of the negative electrode, independent of the solid electrolyte layer.

[0147] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing the decrease in battery capacity, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1 to 5 wt% based on the total weight of the electrolyte.

[0148] As described above, the lithium secondary battery including the positive electrode active material according to the present invention stably exhibits excellent discharge capacity, output characteristics and life characteristics, and is therefore useful in the fields of portable devices such as mobile phones, notebook computers, and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).

[0149] The external shape of the lithium secondary battery according to the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, etc. Furthermore, the lithium secondary battery can be used not only as a battery cell used as a power source for a small device, but also preferably as a unit battery for a medium- to large-sized battery module including a plurality of battery cells.

[0150] According to yet another aspect of the present invention, there may be provided a battery module including the lithium secondary battery as a unit cell and / or a battery pack including the same.

[0151] The battery module or the battery pack can be used as a power source for one or more medium- to large-sized devices, such as a power tool, an electric vehicle (Electric Vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV), or a power storage system.

[0152] The present invention will be described in more detail below with reference to examples. However, these examples are for the purpose of illustrating the present invention, and the scope of the present invention is not to be construed as being limited by these examples.

[0153] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may usually have a thickness of 3 to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive strength of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0154] The positive electrode active material layer may be prepared by coating a positive electrode slurry composition containing the positive electrode active material, a conductive material, and optionally a binder, on the positive electrode current collector.

[0155] At this time, the positive electrode active material may be included in a content of 80 wt% to 99 wt%, more specifically, 85 wt% to 98.5 wt%, based on the total weight of the positive electrode active material layer, and excellent capacity characteristics can be exhibited when the content is within this range, but is not necessarily limited thereto.

[0156] The conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the battery that is constructed. Specific examples include graphite such as natural graphite and artificial graphite, carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon-based materials such as carbon fibers, metal powders or metal fibers such as copper, nickel, aluminum, and silver, conductive whiskers such as zinc oxide and potassium titanate, conductive metal oxides such as titanium oxide, and conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in combination. The conductive material may be contained in an amount of 0.1 wt% to 15 wt% based on the total weight of the positive electrode active material layer.

[0157] The binder serves to improve the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof, and among these, one type alone or a mixture of two or more types may be used. The binder may be included in an amount of 0.1 to 15 wt% based on the total weight of the positive electrode active material layer.

[0158] The positive electrode may be manufactured by a typical method for manufacturing a positive electrode, except for using the positive electrode active material. Specifically, the positive electrode may be manufactured by dissolving or dispersing the positive electrode active material and, optionally, a binder and a conductive material in a solvent to prepare a positive electrode slurry composition, which is then coated on a positive electrode current collector, followed by drying and rolling.

[0159] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, and to provide a viscosity that allows excellent thickness uniformity when applied to manufacture a positive electrode, taking into consideration the coating thickness of the slurry and the production yield.

[0160] In another embodiment, the positive electrode may be manufactured by casting the positive electrode slurry composition on a separate support, peeling the positive electrode slurry composition from the support, and laminating the resulting film on a positive electrode current collector.

[0161] According to yet another aspect of the present invention, there may be provided an electrochemical device including the above-mentioned positive electrode. The electrochemical device may be, for example, a battery or a capacitor, and more specifically, a lithium secondary battery.

[0162] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode facing the positive electrode, and a separator and an electrolyte interposed between the positive electrode and the negative electrode. Here, since the positive electrode is as described above, a detailed description thereof will be omitted for convenience, and only the remaining components not described above will be described in detail below.

[0163] The lithium secondary battery may optionally further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.

[0164] The negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0165] The negative electrode current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may generally have a thickness of 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector may be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.

[0166] The negative electrode active material layer may be prepared by coating a negative electrode slurry composition containing the negative electrode active material, a conductive material, and optionally a binder, on the negative electrode current collector.

[0167] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon, metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys, and SiO β (0<β<2), SnO 2, a metal oxide capable of doping and dedoping lithium, such as vanadium oxide or lithium vanadium oxide, or a composite containing the metallic compound and a carbonaceous material, such as a Si-C composite or a Sn-C composite, may be used. Any one or a mixture of two or more of these may be used. A thin film of metallic lithium may be used as the negative electrode active material. In addition, both low-crystalline carbon and high-crystalline carbon may be used as the carbon material. Representative examples of low-crystalline carbon include soft carbon and hard carbon, and representative examples of high-crystalline carbon include amorphous, plate-like, scaly, spherical or fibrous natural graphite or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes.

[0168] The negative electrode active material may be included in an amount of 80 wt % to 99 wt % based on the total weight of the negative electrode active material layer.

[0169] The binder is a component that aids in bonding between the conductive material, the active material, and the current collector, and may be added in an amount of 0.1 wt% to 10 wt% based on the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.

[0170] The conductive material may be added as a component for further improving the conductivity of the negative electrode active material in an amount of 10 wt% or less, preferably 5 wt% or less, based on the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it has conductivity without inducing a chemical change in the battery, and may be, for example, graphite such as natural graphite or artificial graphite, carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black, conductive fibers such as carbon fibers or metal fibers, metal powders such as carbon fluoride, aluminum, or nickel powder, conductive whiskers such as zinc oxide or potassium titanate, conductive metal oxides such as titanium oxide, or conductive materials such as polyphenylene derivatives.

[0171] In one embodiment, the negative electrode active material layer may be prepared by coating a negative electrode slurry composition prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent on a negative electrode current collector and drying the coating. Alternatively, the negative electrode slurry composition may be cast on a separate support, and then peeled off from the support to obtain a film, which may be laminated on the negative electrode current collector.

[0172] In another embodiment, the negative electrode active material layer may be manufactured by coating a negative electrode slurry composition prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent on a negative electrode current collector and drying the coating, or by casting the negative electrode slurry composition on a separate support and peeling the composition from the support to obtain a film, which may be laminated on the negative electrode current collector.

[0173] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode to provide a passage for lithium ions to move. Any separator generally used in lithium secondary batteries may be used without any particular limitation. In particular, it is preferable that the separator has low resistance to ion movement of the electrolyte and has excellent electrolyte humidification ability. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high-melting point glass fiber, a polyethylene terephthalate fiber, or the like, may be used. In addition, in order to ensure heat resistance or mechanical strength, a separator coated with a ceramic component or a polymer material may be used, and may be selectively used as a single-layer or multi-layer structure.

[0174] Furthermore, examples of the electrolyte used in the present application include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the manufacture of lithium secondary batteries, but are not limited to these.

[0175] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0176] The organic solvent may be used without any particular limitation as long as it serves as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone, an ether solvent such as dibutyl ether or tetrahydrofuran, a ketone solvent such as cyclohexanone, an aromatic hydrocarbon solvent such as benzene or fluorobenzene, dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Examples of the solvents that may be used include carbonate-based solvents such as ethylene carbonate (PC), alcohol-based solvents such as ethyl alcohol and isopropyl alcohol, nitriles such as R-CN (R is a straight-chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can improve the charge / discharge performance of a battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred. In this case, the performance of the electrolyte may be excellent if the cyclic carbonate and the chain carbonate are mixed at a volume ratio of about 1:1 to about 1:9.

[0177] The lithium salt may be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. 6 , LiClO 4 , LiAsF 6 , LiBF 4 , LiSbF 6 , LiAlO 4 , LiAlCl 4 , LiCF 3 SO 3 , LiC 4 F 9 SO 3 , LiN(C 2 F 5 SO 3 ), LiN(C 2 F 5 SO 2 ) 2 , LiN(CF 3 SO 2 ) 2 , LiCl, LiI, or LiB(C 2 O 4 ) 2 The lithium salt may be used at a concentration within the range of 0.1 to 2.0 M. When the lithium salt concentration is within this range, the electrolyte has appropriate conductivity and viscosity, and therefore excellent electrolyte performance can be exhibited, and lithium ions can migrate effectively.

[0178] When the electrolyte used in the present application is a solid electrolyte, for example, a solid inorganic electrolyte such as a sulfide-based solid electrolyte, an oxide-based solid electrolyte, a nitride-based solid electrolyte, or a halide-based solid electrolyte may be used, and preferably, a sulfide-based solid electrolyte may be used.

[0179] As the material of the sulfide-based solid electrolyte, a solid electrolyte containing Li, an X element (wherein X is at least one selected from P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In) and S may be used. Examples of the sulfide-based solid electrolyte material include Li 2 SP2 S 5 , Li 2 SP 2 S-LiX (where X is a halogen element such as I or Cl), Li 2 SP 2 S 5 -Li 2 O, Li 2 SP 2 S 5 -Li 2 O-LiI, Li 2 S-SiS 2 , Li 2 S-SiS 2 - LiI, Li 2 S-SiS 2 -LiBr, Li 2 S-SiS 2 -LiCl, Li 2 S-SiS 2 -B 2 S 3 - LiI, Li 2 S-SiS 2 -P 2 S5-LiI, Li 2 S.B. 2 S 3 , Li 2 SP 2 S 5 -ZmSn (where m and n are integers and Z is Ge, Zn or Ga), Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 2 S-SiS 2 -Li p MO q (where p, q are integers and M is P, Si, Ge, B, Al, Ga or In).

[0180] The solid electrolyte, preferably the sulfide-based solid electrolyte, may be amorphous or crystalline, or may be in a mixed amorphous and crystalline state.

[0181] As a material for oxide-based solid electrolytes, Li7 La 3 Zr 2 O 12 , Li 7-x La 3 Zr 1-x Nb x O 12 , Li 7-3x La 3 Zr 2 Al x O 12 , Li 3x La 2 / 3-x TiO 3 , Li 1+x Al x Ti 2-x (PO 4 ) 3 , Li 1+x Al x Ge 2-x (PO 4 ) 3 , Li 3 PO 4 , Li 3+x PO 4-x N x (LiPON), Li 2+2x Zinc 1-x GeO 4 (LISICON), etc.

[0182] The solid electrolyte may be disposed as a separate layer (solid electrolyte layer) between the positive electrode and the negative electrode. The solid electrolyte may be included in a portion of the positive electrode active material layer of the positive electrode, independent of the solid electrolyte layer, or the solid electrolyte may be included in a portion of the negative electrode active material layer of the negative electrode, independent of the solid electrolyte layer.

[0183] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing the decrease in battery capacity, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1 to 5 wt% based on the total weight of the electrolyte.

[0184] As described above, the lithium secondary battery including the positive electrode active material according to the present invention stably exhibits excellent discharge capacity, output characteristics and life characteristics, and is therefore useful in the fields of portable devices such as mobile phones, notebook computers, and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).

[0185] The external shape of the lithium secondary battery according to the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, etc. Furthermore, the lithium secondary battery can be used not only as a battery cell used as a power source for a small device, but also preferably as a unit battery for a medium- to large-sized battery module including a plurality of battery cells.

[0186] According to yet another aspect of the present invention, there may be provided a battery module including the lithium secondary battery as a unit cell and / or a battery pack including the same.

[0187] The battery module or the battery pack can be used as a power source for one or more medium- to large-sized devices, such as a power tool, an electric vehicle (Electric Vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV), or a power storage system.

[0188] The present invention will be described in more detail below with reference to examples. However, these examples are for the purpose of illustrating the present invention, and the scope of the present invention is not to be construed as being limited by these examples.

[0189] Production Example 1. Production of positive electrode active material Comparative Example 1 Using a known co-precipitation method, nickel sulfate and manganese sulfate were mixed in a 75:25 molar ratio in an aqueous solution to prepare Ni particles with an average particle size of about 3 μm. 0.75 Mn 0.25 (OH) 2 Precursor (small grain precursor) and Ni with an average grain size of about 12 μm 0.75 Mn 0.25 (OH) 2 The precursors (large grain precursors) were synthesized separately.

[0190] Next, the precursor mixture in which the small particle precursor and the large particle precursor were mixed in a weight ratio of 3:7 was mixed with LiOH (Li / (metal excluding Li) molar ratio = 1.05 ± 0.05), and then O 2 First heat treatment for 12 h at 830 °C in O atmosphere. 2 The final product (bimodal) was obtained by a second heat treatment at 700° C. for 12 hours in an atmospheric condition.

[0191] Comparative Example 2 Using a known co-precipitation method, nickel sulfate and manganese sulfate were mixed in a 75:25 molar ratio in an aqueous solution to prepare Ni particles with an average particle size of about 3 μm. 0.75 Mn0.25 (OH) 2 Precursor (small grain precursor) and Ni with an average grain size of about 12 μm 0.75 Mn 0.25 (OH) 2 The precursors (large grain precursors) were synthesized separately.

[0192] Next, the precursor mixture in which the small particle precursor and the large particle precursor were mixed in a weight ratio of 7:3 was mixed with LiOH (Li / (metal excluding Li) molar ratio = 1.05 ± 0.05), and then O 2 The first heat treatment was performed at 830° C. for 12 hours in an atmosphere to obtain an intermediate product.

[0193] Next, the intermediate product and Co 3 O 4 (Weigh out so that the mole fraction of cobalt in the metal elements excluding lithium is 0.02 based on the overall composition of the final product (bimodal)) and then mix them. 2 The second heat treatment was performed at 700° C. for 12 hours in a nitrogen atmosphere to obtain a final product (bimodal) on which a cobalt-containing coating layer was formed.

[0194] Comparative Example 3 Using a known co-precipitation method, nickel sulfate and manganese sulfate were mixed in a 75:25 molar ratio in an aqueous metal salt solution to prepare Ni particles with an average particle size of about 12 μm. 0.75 Mn 0.25 (OH) 2 A precursor (large-grain precursor) was synthesized.

[0195] Next, the large-grain precursor was mixed with LiOH (Li / (Li-excluded metal) molar ratio = 1.05 ± 0.05), and then O 2 The first heat treatment was performed at 800 °C for 12 h in an O atmosphere. 2 The second heat treatment was performed at 700° C. for 12 hours in an atmosphere to obtain the final product (large particles).

[0196] Comparative Example 4 Using a known co-precipitation method, nickel sulfate and manganese sulfate were mixed in a 75:25 molar ratio in an aqueous solution to prepare Ni particles with an average particle size of about 3 μm. 0.75 Mn 0.25 (OH) 2 The precursor (small precursor) was synthesized.

[0197] Next, the small-grain precursor was mixed with LiOH (Li / (Li-excluded metal) molar ratio = 1.05 ± 0.05), and then O 2 The first heat treatment was performed at 800 °C for 12 h in an O atmosphere. 2 The final product (small particles) was obtained by a second heat treatment at 700° C. for 12 hours in an atmosphere.

[0198] Comparative Example 5 Using a known co-precipitation method, nickel sulfate and manganese sulfate were mixed in a 75:25 molar ratio in an aqueous solution to prepare Ni particles with an average particle size of about 3 μm. 0.75 Mn 0.25 (OH) 2 The precursor (small precursor) was synthesized.

[0199] Next, the small-grain precursor was mixed with LiOH (Li / (Li-excluded metal) molar ratio = 1.05 ± 0.05), and then O 2 The first heat treatment was performed at 800° C. for 12 hours in an atmosphere to obtain an intermediate product.

[0200] Next, the intermediate product and Co 3 O 4 (Weigh out so that the mole fraction of cobalt in the metal elements excluding lithium is 0.02 based on the overall composition of the final product (small particles)) and then mix them. 2 The second heat treatment was performed at 700° C. for 12 hours in an atmosphere to obtain a final product (small particles) on which a cobalt-containing coating layer was formed.

[0201] Example 1 Using a known co-precipitation method, nickel sulfate, cobalt sulfate, and manganese sulfate were mixed in a molar ratio of 91:8:1 to prepare nickel sintered bodies with an average particle size of about 3 μm. 0.91 Co 0.08 Mn 0.01 (OH) 2 The precursor (small precursor) was synthesized.

[0202] Next, the small-grain precursor was mixed with LiOH (Li / (Li-excluded metal) molar ratio = 1.05 ± 0.05), and then O 2 After the first heat treatment at 800° C. for 12 hours in an atmosphere, the mixture was vacuum dried at 120° C. and washed with water to obtain an intermediate product.

[0203] Next, the intermediate product and Co 3 O 4 (Weigh out so that the mole fraction of cobalt in the metal elements excluding lithium is 0.03 based on the overall composition of the final product (small particles)) and then mix them. 2 The final product (small particles) was obtained by a second heat treatment at 700° C. for 12 hours in an atmosphere.

[0204] Then, the final product (small particles) and the final product (large particles) prepared in Comparative Example 3 were mixed in a weight ratio of 1:9 to obtain a final product (bimodal).

[0205] Example 2 A final product (bimodal) was prepared in the same manner as in Example 1, except that the final product (small particles) and the final product (large particles) prepared in Comparative Example 3 were mixed in a weight ratio of 2:8.

[0206] Example 3 A final product (bimodal) was prepared in the same manner as in Example 1, except that the final product (small particles) and the final product (large particles) prepared in Comparative Example 3 were mixed in a weight ratio of 3:7.

[0207] Example 4 Using a known co-precipitation method, nickel sulfate and manganese sulfate were mixed in a 75:25 molar ratio in an aqueous metal salt solution to prepare Ni particles with an average particle size of about 12 μm. 0.75 Mn 0.25 (OH) 2 A precursor (large-grain precursor) was synthesized.

[0208] Next, the large-grain precursor was mixed with LiOH (Li / (Li-excluded metal) molar ratio = 1.05 ± 0.05), and then O 2 The first heat treatment was performed at 800° C. for 12 hours in an atmosphere to obtain an intermediate product.

[0209] Next, the intermediate product and Co 3 O 4 (Weigh out so that the mole fraction of cobalt in the metal elements excluding lithium is 0.01 based on the overall composition of the final product (large particles)) and then mix them. 2 The second heat treatment was performed at 700° C. for 12 hours in a nitrogen atmosphere to obtain a final product (large particles) on which a cobalt-containing coating layer was formed.

[0210] Thereafter, the final product (small particles) prepared in Example 1 and the final product (large particles) were mixed in a weight ratio of 1:9 to obtain a final product (bimodal).

[0211] The composition of the positive electrode active material (final product) prepared in Preparation Example 1 was confirmed through ICP analysis and is shown in Table 1 below.

[0212] [Table 1]

[0213] Manufacturing example 2. Manufacturing of lithium secondary battery (half cell) A positive electrode slurry was prepared by dispersing 94 wt% of the positive electrode active material prepared in Preparation Example 1, 3 wt% of carbon black, and 3 wt% of PVDF binder in 30 g of N-methyl-2-pyrrolidone (NMP). The positive electrode slurry was uniformly applied to a thin aluminum film having a thickness of 15 μm and dried in a vacuum at 135° C. to prepare a positive electrode for a lithium secondary battery.

[0214] Lithium foil was used as the counter electrode for the positive electrode, a porous polyethylene film (Celgard 2300, thickness: 25 μm) was used as the separator, and LiPF was dissolved in a solvent of ethylene carbonate and ethyl methyl carbonate mixed in a volume ratio of 3:7. 6 A half-cell was fabricated using an electrolyte in which Zn was present at a concentration of 1.15M.

[0215] Experimental Example 1. Analysis of the crystal structure of the positive electrode active material The lithium secondary batteries prepared in Preparation Example 2 using the positive electrode active materials according to Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to a two-cycle formation process at 25° C., voltage range of 3.0 V to 4.4 V, and 0.1 C / 0.1 C using an electrochemical analyzer (Toyo, Toscat-3100), and then charged and discharged at 25° C., voltage range of 3.0 V to 4.4 V, and 0.1 C / 0.1 C.

[0216] At this time, the voltage (V) and battery capacity (Q) measured during initial discharge under the charge / discharge conditions were used, the X-axis was the voltage (V) and the Y-axis was the battery capacity (Q), and the battery capacity (Q) was differentiated with respect to the voltage (V) to obtain a dQ / dV profile.

[0217] FIG. 2 is a graph showing the dQ / dV profiles during initial discharge of lithium secondary batteries manufactured using the positive electrode active materials according to Examples 1 to 3, respectively, and FIG. 3 is a graph showing the dQ / dV profiles during initial discharge of lithium secondary batteries manufactured using the positive electrode active materials according to Comparative Examples 1 to 3, respectively.

[0218] 2 and 3, it can be seen that in the case of the lithium secondary batteries using the positive electrode active materials according to Examples 1 to 3, a peak exists in the charging region in the voltage range of about 4.1 V to about 4.2 V, whereas in the case of the lithium secondary batteries using the positive electrode active materials according to Comparative Examples 1 to 3, no such peak exists in the voltage range of about 4.2 V or less.

[0219] That is, according to the above results, it can be confirmed that the lithium secondary batteries using the positive electrode active materials according to Comparative Examples 1 to 3 can exhibit appropriate capacity in a voltage range of about 4.3 V, whereas the lithium secondary batteries using the positive electrode active materials according to Examples 1 to 3 can exhibit appropriate capacity in a voltage range lower than 4.2 V.

[0220] Experimental Example 2: Evaluation of the electrochemical characteristics of a lithium secondary battery (half cell) The lithium secondary battery (half cell) prepared in Preparation Example 2 was subjected to a charge-discharge experiment at 25° C., voltage range of 3.0 V to 4.3 V, and discharge rate of 0.1 C using an electrochemical analyzer (Toyo, Toscat-3100) to measure the initial charge capacity, initial discharge capacity, and initial efficiency.

[0221] In addition, the same lithium secondary battery (half cell) was charged and discharged 50 times at 25°C, voltage range of 3.0V to 4.3V, and 1C / 1C using an electrochemical analyzer (Toyo, Toscat-3100), and the ratio of the discharge capacity at the 50th cycle to the initial capacity (cycle capacity retention) was measured.

[0222] The measurement results are shown in Table 2 below.

[0223] [Table 2]

[0224] Referring to the results in Table 2, it can be seen that the electrochemical properties of the bimodal type positive electrode active material containing a nickel-based lithium composite oxide containing cobalt and a cobalt-free lithium composite oxide are better than those of Comparative Examples 1 and 2, which are bimodal type positive electrode active materials consisting only of small and large particles of a cobalt-free composition.

[0225] In addition, referring to the results of Comparative Example 1 and Comparative Example 2, even if the positive electrode active material of Comparative Example 1 was coated with cobalt so that the cobalt was present at an appropriate level based on the overall composition of the bimodal type positive electrode active material, no significant change due to the cobalt coating was observed as long as the bulk particles themselves were cobalt-free.

[0226] Experimental Example 3: Analysis of residual lithium in positive electrode active material The residual lithium (lithium impurity) content in the positive electrode active material prepared according to Preparation Example 1 was analyzed by pH titration. In the pH titration, the residual lithium (lithium impurity) content was measured by the amount of 0.1M HCl used until the pH reached 4 by pH titration of the positive electrode active material. Specifically, 5 g of each positive electrode active material prepared according to Preparation Example 1 was placed in 100 ml of DIW, stirred for 15 minutes, and filtered. 50 ml of the filtered solution was taken, to which 0.1M HCl was added, and the amount of HCl consumed due to the change in pH was measured. The amounts of LiOH and Li 2 CO 3 The total content was calculated.

[0227] The measurement results are shown in Table 3 below.

[0228] [Table 3]

[0229] Referring to the results in Table 3, it can be seen that the residual lithium content in the positive electrode active material according to the Examples is generally lower than that of the positive electrode active material according to the Comparative Examples. When the coating process is performed on the bulk particles, the coating raw material reacts with the residual lithium present on the surface of the bulk particles to form a coating layer, resulting in a decrease in the residual lithium content. Nevertheless, considering that the residual lithium content measured in the positive electrode active materials according to Comparative Examples 2 and 5, which were subjected to the cobalt coating process, was higher than that of the Examples, it can be seen that the generation of residual lithium was further suppressed in the bimodal type positive electrode active material using a suitable combination of a nickel-based lithium composite oxide containing cobalt and a cobalt-free lithium composite oxide.

[0230] As a result, the residual lithium (LiOH and Li 2 CO 3 The content of (the total content of) can be controlled to 5,000 ppm or less, preferably 4,500 ppm or less.

[0231] Although the embodiments of the present invention have been described above, a person having ordinary knowledge in the art may modify and change the present invention in various ways by adding, changing, deleting or adding elements without departing from the concept of the present invention described in the claims, and this may also be considered to be within the scope of the claims of the present invention.

Claims

1. A bimodal type positive electrode active material comprising a first lithium composite oxide and a second lithium composite oxide having an average particle size larger than that of the first lithium composite oxide, The first lithium composite oxide includes first bulk particles containing at least nickel and cobalt, The second lithium composite oxide comprises cobalt-free second bulk particles.

2. 2. The cathode active material of claim 1, wherein a mole fraction of nickel in the first bulk particles is greater than a mole fraction of nickel in the second bulk particles.

3. 2 . The cathode active material of claim 1 , wherein a mole fraction of manganese in the first bulk particles is less than a mole fraction of manganese in the second bulk particles.

4. The positive electrode active material according to claim 1 , wherein a mole fraction of nickel in metal elements excluding lithium in the first bulk particles is greater than 0.

75.

5. The positive electrode active material according to claim 1 , wherein a mole fraction of cobalt in metal elements excluding lithium in the first bulk particles is 0.15 or less.

6. The positive electrode active material of claim 1 , wherein the first bulk particles are represented by Formula 1: [Chemical formula 1] Li w Ni 1-(x+y+z) Co x M1 y M2 z O 2 (where: M1 is at least one selected from Mn and Al; M2 is at least one selected from P, Sr, Ba, B, Ce, Cr, Mn, Mo, Na, K, Ti, Zr, Al, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, Ca, Ga, Sb, Fe, Nd and Cu; M1 and M2 are different from each other, 0.5≦w≦1.5, 0<x≦0.40, 0≦y≦0.30, 0≦z≦0.20)

7. The positive electrode active material of claim 1 , wherein the second bulk particles are represented by Formula 2: [Chemical formula 2] Li a ii 1-(b+c) 73 b 74 c 9 2-α 8 α (where: M3 is at least one selected from Mn and Al; M4 is at least one selected from Sr, Ba, B, Ce, Cr, Mn, Mo, Na, K, Ti, Zr, Al, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, Ca, Ga, Sb, Fe, Nd and Cu; M3 and M4 are different elements, X is at least one anionic element selected from F, P, S, Cl and Br; 0.5≦a≦1.5, 0≦b≦0.50, 0≦c≦0.20, 0≦α≦0.20)

8. a coating layer is present on at least a portion of the surface of the first bulk particle; The positive electrode active material of claim 1 , wherein the coating layer comprises a metal oxide represented by the following Chemical Formula 3: [Chemical formula 3] Li d M5 e O f (where: M5 is at least one selected from Ni, Co, P, Sr, Ba, B, Ce, Cr, Mn, Mo, Na, K, Ti, Zr, Al, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, Ca, Ga, Sb, Fe, Nd, and Cu, and 0≦d≦8, 0<e≦8, and 0<f≦13.

9. The positive electrode active material of claim 8 , wherein the coating layer present on the surface of the first bulk particles comprises a cobalt-containing oxide.

10. a coating layer is present on at least a portion of the surface of the second bulk particle; The positive electrode active material of claim 1 , wherein the coating layer comprises a metal oxide represented by the following Chemical Formula 4: [Chemical formula 4] Li g M6 h O i (where: M6 is at least one selected from Ni, Co, P, Sr, Ba, B, Ce, Cr, Mn, Mo, Na, K, Ti, Zr, Al, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, Ca, Ga, Sb, Fe, Nd, and Cu, and 0≦g≦8, 0<h≦8, and 0<i≦13.

11. The positive electrode active material of claim 10 , wherein the coating layer present on the surface of the second bulk particles comprises a cobalt-containing oxide.

12. 2. The positive electrode active material according to claim 1, wherein a molar fraction of cobalt in metal elements excluding lithium based on an overall composition of the positive electrode active material including the first lithium composite oxide and the second lithium composite oxide is 0.05 or less.

13. 2. The positive electrode active material according to claim 1, wherein a molar fraction of manganese in metal elements excluding lithium based on an overall composition of the bimodal type positive electrode active material including the first lithium composite oxide and the second lithium composite oxide is 0.10 or more and 0.40 or less.

14. When a lithium secondary battery having the positive electrode active material as a positive electrode and lithium foil as a negative electrode is charged and discharged at 25° C., a voltage range of 3.0 V to 4.4 V, and a discharge rate of 0.1 C, In a graph having a voltage (V) and a battery capacity (Q) at the time of initial discharge, the X-axis is the voltage (V), the Y-axis is the battery capacity (Q), and the battery capacity (Q) is differentiated by the voltage (V) (dQ / dV), The positive electrode active material according to claim 1, wherein there is a peak in the charging region in a voltage range of 4.1 V to 4.2 V.

15. a coating layer is present on at least a portion of the surface of the second bulk particle; 2. The positive electrode active material of claim 1, wherein the coating layer comprises a compound represented by LiX', where X' is an anion element selected from F, Cl, and Br.

16. A positive electrode comprising the positive electrode active material according to claim 1 .

17. A lithium secondary battery using the positive electrode according to claim 16.

Citation Information

Patent Citations

  • Lithium secondary battery

    JP1996264183A

  • Positive electrode active material and nonaqueous electrolyte secondary battery

    JP2005228706A

  • Positive electrode active material for lithium secondary battery, manufacturing method thereof, and lithium secondary battery containing the same

    JP2023026409A

  • Positive electrode active material for non-aqueous electrolyte secondary cell, and non-aqueous electrolyte secondary cell

    WO2013038918A1

  • Positive electrode active material for non-aqueous electrolyte secondary batteries, and non-aqueous electrolyte secondary battery

    WO2024024364A1